Heath Beliefs of UK South Asians Related to Lifestyle Diseases: A Review of Qualitative Literature - Anna Lucas; Esther Murray; Sanjay Kinra (Hindawi Limited, 2013)
Objective. To review available qualitative evidence in the literature for health beliefs and perceptions specific to UK South Asian adults. Exploring available insight into the social and cultural constructs underlying perceptions related to health behaviours and lifestyle-related disease. Methods. A search of central databases and ethnic minority research groups was augmented by hand-searching of reference lists. For included studies, quality was assessed using a predetermined checklist followed by metaethnography to synthesise the findings, using both reciprocal translation and line-of-argument synthesis to look at factors impacting uptake of health behaviours. Results. A total of 10 papers varying in design and of good quality were included in the review. Cultural and social norms strongly influenced physical activity incidence and motivation as well as the ability to engage in healthy eating practices. Conclusions. These qualitative studies provide insight into approaches to health among UK South Asians in view of their social and cultural norms. Acknowledgement of their approach to lifestyle behaviours may assist acceptability of interventions and delivery of lifestyle advice by health professionals.